LT-RT PORTAL VIEN RATIO IN SONOGRAPHIC DIAGNOSIS OF ALCOHOLIC LIVER DISEASE - Al Obeidy, Aswad (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Alcohol remains the single most significant cause of liver disease throughout the Western world, responsible for between 40 and 80% of cases of cirrhosis in different countries. There are no characteristic sonographic features of ALD. Many of the factors underlying the development of alcoholic liver injury remain unknown, and significant questions remain about the value of even very basic therapeutic strategies.Patients and Methods: A total number of 50 patients with ALD were studied. Abdominal Doppler ultrasonography to determine the ratio of the left to right portal vein (PV) was done. They were compared with 50 healthy persons (control) and 50 patients with comparable CLD due to other causes.Results: The diameter of the LT PV was 10.78 +3.37, 7.92 ± 1.56, 9.9 ±2.37 mm in study group, healthy control and CLD (not alcoholic) respectively. The diameter of the RT PV was 9.13 ± 1.96, 9.05 ± 1.59, 9.7 ± 3.37 mm in study group, healthy control and CLD (not alcoholic) respectively. The largest diameter of the LT PV was 19.2 mm and RT PV was 19.3mm. The smallest diameter of the LT PV was 4.8 mm and RT PV was 4.7 mm. There was significant correlation between LT-TR PV ratio of one or more and ALD.In conclusion: The LT-RT PV ratio equal to or more than one was valid in sonographgic finding in the diagnosis of ALD